A just forgiveness : responsible healing without excusing injustice - Worthington, Everett L., 1946- (Downers Grove, Ill. : IVP Books, 2009)
Psychologist Everett L. Worthington, Jr., examines the Christian foundations for just forgiveness and discusses how Christians can forgive wrongdoing without excusing it.
Introduction -- Understanding just forgiveness -- Tensions and questions -- Humility -- Justice -- Forgiveness -- Dealing with wrongdoers -- Living out just forgiveness -- Just forgiveness in the family -- Just forgiveness in the church -- Just forgiveness in communities and society -- Just forgiveness in the world -- What can we do?
Includes bibliographical references (pages [233]-240) and indexes.
Description based on print version record.
Keywords: Forgiveness of sin; Forgiveness -- Religious aspects -- Christianity; Christianity and justice; Christianity and justice; Forgiveness of sin; Forgiveness -- Religious aspects -- Christianity; RELIGION / Christian Theology / Soteriology; Electronic books